Narrativas religiosas no ensino superior em música: uma abordagem (auto)biográfica - Reck, André Müller (2017)
Proceeding from a perspective in musical education which takes as fundamental the daily experience, this work, developed in the line of research 4 (Education and Arts) at the Postgraduation Program in Education of Universidade Federal de Santa Maria- PPGE/UFSM, takes place in the dialogue between the living world and the formative process in higher education in music. Such a research proposes to investigate how the biographical dimension can be discussed in higher education in music and assumes a specific shape by questioning how (and whether) the religious experiences, narrated by an (auto) biographical approach, may be significant in higher formation, emphasizing the discussion in the field of teacher formation in music. The theoretical background seeks elements of reflection in musical education sociology, particularly in its links with the quotidian theories, and also in absents sociology, which considers the ecology of the knowledge as a possibility of achievement in the contemporary world. The producing of data has been fulfilled during a Complementary Subject of Graduating offered in the course of Music of Universidade Federal de Santa Maria, by several entries: 11 (eleven) class diaries, 37 (thirty-seven) written reports, 2 (two) group reports and 8 (eight) individual interviews. This methodology, understood in qualitative perspective, belongs to the methodological-theoretical framework discussed in the field of the (auto) biographical researches as it takes by object of studding the social individual genesis in the biographical processes. Through a hermeneutical focus, the analysis here developed deal with: a) the possibility of understanding the histories of life and musical memories as relevant processes in/for musical formation; b) the relation of religious/spiritual meanings in this formation process; c) in the dialogues between musical narratives, developed during a collective rearrange practice. Such interpretations suggest that it is possible to think higher education in music from some ecology of knowledge, overcoming the monocultural paradigm which still seems to be predominant in this scope of study. Finally, it highlights some subjects in music education which may be enriched by this work: the deepening of the theoretical considerations on religion/religiosity/spirituality and the considering of the biographical dimension in the music teachers formation.